Sustainability Assessment and Optimization in Construction Site: A Simulation-Based Approach - Schlosser, Alexander; Schuderer, Peter; Franke, Jörg (Decarbonizing Value Chains, 2025)
The construction industry is currently facing significant challenges. In order to address these challenges, the REMUS simulation model library for the construction industry is being developed. To this end, the physical modules are divided into stationary and mobile modules, as well as information objects. To create the simulation model and conduct the simulation experiment, a requirements cluster with the most important parameters of construction sites is created. The elements of sustainability—environmental, economy, and social aspects—are employed to assess the simulation results and to optimize the model. To this end, corresponding KPIs, methods, and procedures are delineated, which are documented during the various simulation experiments and evaluated subsequently. The equipment and environment exert an influence on the “economy”. This is reflected in the costs associated with the model components and their operation. The area of “environmental” is represented by the consumption of input materials. Alternative consumption and recovery concepts are implemented and compared here. The “social” aspect is represented by the human-machine collaboration. As part of the simulation experiments, the recorded variables are continuously adapted and refined. This process enables the simulation to improve the sustainability of the construction site environmen